Analysis of Demographic Factors Affecting Mental Health Among Workers at PT X Mining Company in 2023 - Eko Susanto; Mila Tejamaya (CV. Publikasi Indonesia, 2024)
The mining industry is closely related to high-risk health and safety, including mental health. This study aims to investigate the association of demographic variables (age, length of service, gender, education level, employment status, and work location), on mental health symptoms in workers in mining companies PT X. The DASS-21 instrumentation was used to determine mental health symptoms based on levels of depression, anxiety, and stress. The number of respondents in this study was 764 employees were participated and it was found that 71.2% of respondents did not experience mental health problems, 15.3% experienced mild mental health symptoms, 10.4% moderate, and 3.1% severe mental health symptoms. There is a significant relationship between the age variable and the level of depression (p-value 0.04), the significant relationship between age, education level, length of service, gender, and the level of anxiety (p-value 0.04; 0.005; 0.000; dan 0.007), as well as the relationship between age and level of education and stress in workers (p-value 0.000; dan 0.016). From the research, it can be concluded that the older the worker, the lower the level of depression, anxiety, and work stress. Male employees have lower levels of anxiety and stress than women, and a higher level of education plays a role in increasing anxiety and stress in workers.